Становлення та розвиток інституту«право притулку» у міжнародному праві - Колодяжна, В.; Kolodiazhna, V.; Трофимчук, М.; Trofymchuk, M. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У роботі висвітлено становлення та розвиток інституту права притулку та досліджено формування терміну « право притулку», охарактеризовано його зміст та значення. Здійснено аналіз міжнародних нормативно-правових актів, які регулюють відносини, пов’язані з наданням притулку. Отримано висновок, що право притулку є традиційним інститутом міжнародного права, що реалізується державою через надання особі, що зазнає переслідувань з боку іноземної держави чи групи, права на проживання на своїй території без залучення особи до кримінальної відповідальності. Єдиного міжнародно-правового акта щодо процедури надання притулку наразі немає, тому існує гостра потреба у розробці уніфікованих підходів до вирішення цієї актуальної проблеми. Institute of the Refugee Rights in the international law is one of the most important and at the same problematic issues of thepresent day, directly related to the problem of refugees worldwide. Despite the significance of the right ofasylum, few attempts have been made to investigatethese issues in the historical sources and legal documents. The solution of this problem is impossible without a comprehensive analysis of the institution of asylumin the international law and legislation development in this field. The article sheds light on the problem of formation of the institution of the right of asylum in the international law and represents the analysis of the history of its emergence and development in different periods, laying emphasis on the peculiarities of this right utilization. The article describes the rights granting asylum in the Ancient East, Ancient Greece and Rome, in the Middle Ages and the Reformation times. The author highlights the definition of the «right of asylum», describes its content and meaning. The article also analyzes normative and legal acts governing asylum for refugees procedure at present, namely the «Universal Declaration of Human Rights», «Refugee Convention» and the 1967 Protocol Relating to the Status of Refugees thereto.
Formation and Development of the Institute of the Right of Asylum in the International Law
Keywords: право притулку; релігійний притулок; територіальний притулок; Загальна декларація прав людини; Конвенція про статус біженців; the right of asylum; religious asylum; territorial asylum; the Universal Declaration of Human Rights; the Convention on the Status of Refugees